Threat and vulnerability penetration testing: Linux - Setiawan, Deris (Taiwan Academic Network Management Committee, 2014)
A systematic approach to penetration testing of Redhat Linux operating system is described. Hacking is not an easy task, it requires high effort and perseverance to get access, the ability to gather information, skill of coding, and internet working capability is a must. To prevent from intruders, penetration testing is a comprehensive effort to attempt breaking into a system. In this work the evaluation of performance system is built on Linux operating systems. It can be seen that penetration tests are a useful measurement to check the sanity of network infrastructure and hackable or not.